Review of Pumla Dineo Gqola's Female Fear Factory. (23rd September 2022) - Martin, Jamie
Abstract : This paper reviews the book Female Fear Factory (2021) by Pumla Dineo Gqola. An overview and evaluation of the book are provided, emphasising the important deepening of the central concept and its relevance to anti-rape and feminist work, activism and scholarship across the world.